Optimizing image processing for modern wide field surveys: enhanced data management based on the LSST science pipelines - Hong, Yuanyu; Yang, Chao; Zhang, Miaomiao; Chen, Yanpeng; Liu, Binyang (Frontiers in Astronomy and Space Sciences, 2024)
In recent decades, numerous large survey projects have been initiated. As a flagship project of the Stage IV cosmology imaging surveys, the Vera C. Rubin Observatory's Legacy Survey of Space and Time (LSST) offers an open-source framework for data management and processing that holds the potential for adaptation to various instruments. Complementing the LSST, upcoming wide field surveys will leverage smaller yet highly flexible systems to provide new scientific perspectives. In this paper, we introduce the obs mccd software package, acting as not only a bridge between raw data from a generic mosaic-CCD instrument and the intrinsic LSST data management framework but also an interface to deploy tailored configurations to the pipeline middleware. To demonstrate the validity of our data processing pipeline, we select a batch of realistic data from a commissioning wide field telescope and process it through our pipeline.In addition, we establish a prototype of the quality control (QC) system, which is capable of assessing image quality such as PSF size and ellipticity, as well as astrometric calibration. Our analysis focuses on the performance of astrometric calibration. We have found that a fifth-order polynomial effectively characterizes geometric distortion, with a median average geometric distortion residual of 0.011 pixel. Additionally, utilizing our in-house pipeline for the same dataset yields a median average geometric distortion residual of 0.016 pixel.